Two new Pseudopestalotiopsis species isolated from Celtis sinensis and Indocalamus tessellatus plants in southern China - Yang, Qi; He, Yu-Ke; Yuan, Jun; Wang, Yong (Phytotaxa, 2022)
Two coelomycetous strains with appendage-bearing conidia were collected from diseased leaves of Celtis sinensis (Urticales, Ulmaceae) and Indocalamus tessellatus (Poales, Poaceae) in Yunnan and Hainan provinces, southern China. Both strains produced 4-septate conidia with concolourous median cells, which were similar to Pestalotiopsis and Pseudopestalotiopsis. Based on the comprehensive morphological comparison and multi-gene (ITS, tub2, tef1) phylogenetic analyses, the strains were found to belong to Pseudopestalotiopsis. They represent two novel taxa and are described as Pseudopestalotiopsis celtidis and P. indocalami.